Single-cell transcriptome analysis reveals T-cell exhaustion in denosumab-treated giant cell tumor of bone - Yang, Meiling; Wang, Fen; Lu, Guohao; Cheng, Mingzhe; Zhao, Wei; Zou, Changye (Frontiers in Immunology, 2022)
Denosumab (DMAB), a human monoclonal antibody against the receptor activator of the nuclear factor-kappa B ligand, is used for the treatment for unresectable giant cell tumor of bone (GCTB). However, little is known about the molecular and functional characteristics of GCTB-infiltrating lymphocytes after DMAB treatment. Here, we performed single-cell RNA sequencing and immunostaining assays to delineate the immune landscape of GCTB in the presence and absence of DMAB. We found that exhausted CD8+ T cells were preferentially enriched in DMAB-treated GCTB. A distinct M2-skewed type of tumor-associated macrophages (TAMs) comprises the majority of GCTB TAMs. We identified cytokines, including interleukin-10, and inhibitory receptors of M2 TAMs as important mediators of CD8+ T cell exhaustion. We further revealed that DMAB treatment notably increased the expression levels of periostin (POSTN) in GCTB cells. Furthermore, POSTN expression was transcriptionally regulated by c-FOS signaling and correlated with GCTB recurrence in patients after DMAB treatment. Collectively, our findings reveal that CD8+ T-cells undergo unappreciated exhaustion during DMAB therapy and that GCTB cell-derived POSTN educates TAMs and establishes a microenvironmental niche that facilitates GCTB recurrence.